Improvement, not displacement: A framework for urban green gentrification research and practice. Issue 137 (November 2022) - Sax, Daniel L.; Nesbitt, Lorien; Quinton, Jessica
Abstract: As researchers have continued to expand the bounds of green gentrification scholarship, understanding of what green gentrification is and how to identify the phenomenon on the ground has grown obscured. In an attempt to bring clarity to this conversation, our research presents an urban green gentrification framework, based on findings from a scoping review and dimensional analysis conducted across green gentrification, urban greening, and related literatures. Our study is guided by two primary objectives: (1) identify the key dimensions of green gentrification as it pertains to urban greening; and (2) explore the relationships and intersections between dimensions in terms of their implications for the social impacts and outcomes of urban greening initiatives. We identify three principle dimensions of green gentrification as it relates to urban greening — conceptual foundations ; design and intent ; and socio-spatial change — as well as six related sub-dimensions. Considered in tandem, these dimensions present green gentrification as a dynamic process bound within a history of exploitative, neoliberal social and economic processes, operating beyond the scope of any single urban greening initiative. Responding to green gentrification, therefore, requires trans-dimensional strategies that consider these structural influences guiding patterns of urban greening investment and development. Our results also show that green gentrification is not a sufficient explanation for the complexities of urban development and change, and greening should be considered alongside other drivers of gentrification more broadly. Highlights: We identify three principal dimensions and six sub-dimensions of green gentrification as related to urban greening. Our principal dimensions are conceptual foundations ; design and intent ; and socio-spatial change. Framework shows that green gentrification is a dynamic process rooted in a neoliberal social and economic processes. Green gentrification is a systemic outcome that operates beyond the scope of any single urban greening initiative. Responding to green gentrification requires strategies that consider structural influences.